Thermal Comfort Index Analysis of Padang City Coastal Tour-ism Area Using the Physiological Equivalent Temperature (PET) Method - Sadinda Tsania Suhada; Nofi Yendri Sudiar; Hamdi; Letmi Dwiridal (Journal of Climate Change Society, 2023)
This study aims to determine the category of comfortable thermal sensation in traveling based on the value of the Physiological Equivalent Temperature (PET) thermal index. The research sites were selected in Padang Beach (PP), Air Manis Beach (PAM) and Nirwana Beach (PN). Calculation of perception of comfort using questionnaire data to visitors. PET calculation data is sourced from the Meteorology, Climatology and Geophysics Agency (BMKG) in 2011-2020 and direct measurement data. The results show that the PET thermal sensation category for the Padang City coastal area throughout the year (2011-2020) is included in the "warm" category for tourism activities. Likewise, direct measurements show the "very hot" category with a PET value of 40.3ºC. However, interviews with visitors showed that the overall comfort condition was “neutral” (62%). This is due to environmental conditions that provide a comfortable effect on visitors. The majority of visitors were interviewed under the auspices. Although the measured air temperature is classified as "high", the effects of trees, walking paths and rest areas make visitors feel comfortable.